A PRÁTICA SOCIAL DAS IGREJAS BATISTAS DE CAMPO GRANDE - MS. UMA ANÁLISE HISTÓRICA CONCEITUAL A PARTIR DA PRÁXIS TRANSFORMADORA - Lima, Joaze Barbosa de (2013)
The research aims to study the social practice of Baptist Churches of Campo Grande - MS, in the light of the historical relationship of Baptists to social action and the concepts of transformative praxis. This study focuses on the social actions of the Baptist churches in the city of Campo Grande, analysis and perspective of practical theology, and realize the criteria and ideologies behind these actions. To this end a literature on the history of Baptists from its origin and history of Baptists in Mato Grosso do Sul was held, hoping thereby to see the roots of social practice and their Baptist theological ideologies. The beginning of the research it refers the origin of the Baptists in the early days of Protestantism and its (possible) relationships with social transformation of realities, ideologies and theological principles. Secondly we sought to Baptist history in Mato Grosso do Sul and the city of Campo Grande. Finally, we sought to theorize the light of practical theology social action that is transformative and liberating even in complex situations such as urban reality, pointing out possible paths through a pastoral citizen. The final consideration that arrives this research is that the church has been involved with the social reality of the cities, and when it does, performs simplistically, without due care and preparation, without an engagement in transforming realities cohesive actions . From the Institute could perceive the possibility of having a social practice relevant to government and private support, however, is not perceived interaction, involvement by the church. It is expected then an awakening of the churches in relation to its mission, and possibilities of them in the social field.